Meningkatkan Kemampuan Literasi Dan Bahasa Pada Anak TK B Usia 5-6 Tahun Melalui Kalender Bahasa Di Tkit Robbani Singosari - Kulsum, Umi; Muntomimah, Siti; Akbar, Muhammad Ramli (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2025)
Children aged 5-6 years have literacy skills, including having vocabulary, recognizing literacy or letter symbols in preparation for reading and writing, counting, making simple sentences, having many words to express their ideas to others. Literacy is a part of language development. For this reason, it is necessary to develop language/literacy skills in early childhood. The research methodology used is Class Action Research. The study was conducted in several stages, namely pre-cycle, cycle 1, and Cycle 2. Data collection techniques taken by way of observation and documentation. The assessment indicators started from undeveloped, began to develop, developed as expected, and developed very well. Students of Tkit Robbani Group B Rombel Ilyas literacy and language skills, especially knowing literacy, increased by 85% from the number of 15 students. The child already knows the Letters, connects the sounds of letters and symbols of letters, reads syllables. Children are also more active when communicating in every activity.